Cohesion and Cooperation in sports teams - Olmedilla, Aurelio; Ortega, Enrique; Almeida, Pedro; Lameiras, Joao; Villalonga, Tomás; Sousa, Cristina; Torregrosa, Miquel; Cruz, Jaume; García Mas, Alexandre (Anales de Psicología / Annals of Psychology, 2010)
Cohesion and cooperation are two psychological mechanisms of teams that are theoretically different and relatively independent. The intent of this study was to assess the levels of cohesion and cooperation and the relationships between them, as well as other variables, in a sample of 945 competitive football players between the ages of 12 and 18 years (M = 14.7, SD = 1.8). The results indicate that the factors of athletic cohesion behave almost as one single factor, which is the opposite of what happens with cooperation, and that there is a relationship between uncon- ditional cooperation and cohesion. There is a significant difference be- tween starting and bench players with regard to the conditional coopera- tion and overall cohesion, but there are no differences with regard to player’s position nor with the years of practice. Finally, cohesion may be determined in part by cooperation, while the factor of cohesion of the acceptance of roles has been demonstrated to be relevant for both constructs.